2011
DOI: 10.1017/s0031182011001260
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variations and age effect on Toxoplasma gondii seroprevalence in seals from the Canadian Arctic

Abstract: Toxoplasmosis is a significant public health threat for Inuit in the Canadian Arctic. This study aimed to investigate arctic seals as a possible food-borne source of infection. Blood samples collected from 828 seals in 7 Canadian Arctic communities from 1999 to 2006 were tested for Toxoplasma gondii antibodies using a direct agglutination test. Polymerase chain reaction (PCR) was used to detect T. gondii DNA in tissues of a subsample of seals. Associations between seal age, sex, species, diet, community and ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 42 publications
1
22
1
1
Order By: Relevance
“…Such samples (mixture of blood/tissue fluid) are often the only samples available, particularly in wildlife studies, and are considered a good alternative to serum samples for serological surveys (Tryland et al 2006, Simon et al 2011, Glor et al 2013. However, such samples are often opaque and rich in particulate matter, especially if the carcass has been stored over a long time or frozen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such samples (mixture of blood/tissue fluid) are often the only samples available, particularly in wildlife studies, and are considered a good alternative to serum samples for serological surveys (Tryland et al 2006, Simon et al 2011, Glor et al 2013. However, such samples are often opaque and rich in particulate matter, especially if the carcass has been stored over a long time or frozen.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission routes by which marine animals can become infected are largely un known but likely involve a marine pathway (Jensen et al 2010, Massie et al 2010. Oocysts remain viable in molluscs, in the gills of migratory fish and in seawater (Arkush et al 2003, Lindsay et al 2003, 2004, Massie et al 2010, Shapiro et al 2012, and waterborne transmission is likely (Dubey 2004, WinieckaKrusnell et al 2009, Jones & Dubey 2010, particularly in the Arctic (Jensen et al 2010, Simon et al 2011, 2013. Contamination by oocysts from terrestrial ecosystems has been associated with toxoplasmosis outbreaks in sea otters (Miller et al 2002) and beluga whales (Mikaelian et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasmosis can cause significant mortality (Dubey et al 2003, Bossart 2011 in marine mammals, as shown in studies of southern sea otters Enhydra lutris nereis and other aquatic mammals (Buergelt & Bonde 1983, Di Guardo et al 2011, Dubey et al 2003, Miller et al 2002, Santos et al 2011, Simon et al 2011. Felids are the definitive hosts for T. gondii since they shed viable oocysts in feces that contaminate the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the difficulty to organize long-term surveys, year-to-year variations have been found in a few populations only: in roe deer Capreolus capreolus in Spain [73] and in Sweden [74], in red deer Cervus elaphus in Scotland [75], as well as in Canadian seals [76]. Tizard et al [77] performed the largest survey to our knowledge, with nearly 12,000 persons studied over 14 years.…”
Section: Temporal Dynamicsmentioning
confidence: 99%